Safety of phosphatidylserine containing omega-3 fatty acids in non-demented elderly: a double-blind placebo-controlled trial followed by an open-label extension - Vakhapova, Veronika (BioMed Central, 2011)
BACKGROUND: Phosphatidylserine (PS) is a naturally occurring phospholipid present in the inner leaflet of mammalian plasma membranes. Administration of PS extracted from bovine cortex (BC-PS), which contains high levels of omega-3 long chain polyunsaturated fatty acid (LC-PUFA) attached to its backbone, resulted in positive effects on brain functions such as learning and memory. Recently, a novel marine-sourced PS with omega-3 LC-PUFA attached to its backbone was developed (PS-DHA). In the present study, we evaluated the safety profile of the novel PS preparation in non-demented elderly with memory complaints. The efficacy study of this novel formulation indicated that PS-DHA may ameliorate cognitive deficits in non-demented elderly population. METHODS: 157 non-demented elderly participants with memory complaints were randomized to receive either PS-DHA (300 mg PS/day) or placebo for 15 weeks. Standard biochemical and hematological safety parameters, blood pressure and heart rate were evaluated at baseline and endpoint. 122 participants continued into an open-label extension for additional 15 weeks, in which they all consumed PS-DHA (100 mg PS/day) and were evaluated for their blood pressure, heart rate and weight at endpoint. Adverse events were monitored throughout the double-blind and open-label phases. RESULTS: 131 participants completed the double-blind phase. No significant differences were found in any of the tested safety parameters between the study groups, or within each group. 121 participants completed the open-label phase. At the end of this phase, there was a reduction in resting diastolic blood pressure and a slight weight gain among participants who consumed PS-DHA for 30 weeks. CONCLUSIONS: The results of this study indicate that consumption of PS-DHA at a dosage of 300 mg PS/day for 15 weeks, or 100 mg PS/day for 30 weeks, is safe, well tolerated, and does not produce any negative effects in the tested parameters. TRIAL REGISTRATION: clinicaltrials. gov, identifier: NCT00437983